A parametric study of convective heat transfer on LNG tank by numerical simulations - Guellal, M.; Touabti, A.; Abdesselam, H. (2009)
with precision its behavior at conditions close to the storage real conditions. The proposed method is based on the ADI method. The aim of this study is to carry out a parameter setting of the principal physical properties intervening in the natural convection equations, namely the Rayleigh number characterizing heat exchange, Prandtl number which characterizes the relative importance of the heating and viscous effects, and the aspect ratio describing the tank geometry. The obtained results show that for small values of Rayleigh number a flow exists, and results in weak variations of isotherms. The increase of Rayleigh number causes the increase of the maximum velocity no matter the dimension of the tank. Nevertheless, this increase is more significant in the case of high aspect ratio (less broad tank). We note that the disturbance reaches the center of the tank more quickly when this one is less broad. For the fluids of great Prandtl number (Ethylene glycol for example, Pr = 92.5), the thermal time is larger than viscous time and the heat diffusion processes control the fluid motion.